A Standards-Based Architecture Proposal for Integrating Patient mHealth Apps to Electronic Health Record Systems - Marceglia, S.; Fontelo, P.; Rossi, E.; Ackerman, MJ (Applied Clinical Informatics, 2015)
Summary Background: Mobile health Applications (mHealth Apps) are opening the way to patients’ responsible and active involvement with their own healthcare management. However, apart from Apps allowing patient’s access to their electronic health records (EHRs), mHealth Apps are currently developed as dedicated “island systems”.Objective: Although much work has been done on patient’s access to EHRs, transfer of information from mHealth Apps to EHR systems is still low. This study proposes a standards-based architecture that can be adopted by mHealth Apps to exchange information with EHRs to support better quality of care.Methods: Following the definition of requirements for the EHR/mHealth App information exchange recently proposed, and after reviewing current standards, we designed the architecture for EHR/mHealth App integration. Then, as a case study, we modeled a system based on the proposed architecture aimed to support home monitoring for congestive heart failure patients. We simulated such process using, on the EHR side, OpenMRS, an open source longitudinal EHR and, on the mHealth App side, the iOS platform.Results: The integration architecture was based on the bi-directional exchange of standard documents (clinical document architecture rel2 – CDA2). In the process, the clinician “prescribes” the home monitoring procedures by creating a CDA2 prescription in the EHR that is sent, encrypted and de-identified, to the mHealth App to create the monitoring calendar. At the scheduled time, the App alerts the patient to start the monitoring. After the measurements are done, the App generates a structured CDA2-compliant monitoring report and sends it to the EHR, thus avoiding local storage.Conclusions: The proposed architecture, even if validated only in a simulation environment, represents a step forward in the integration of personal mHealth Apps into the larger health-IT ecosystem, allowing the bi-directional data exchange between patients and healthcare professionals, supporting the patient’s engagement in self-management and self-care.Citation: Marceglia S, Fontelo P, Rossi E, Ackerman MJ. A Standards-Based Architecture Proposal for Integrating Patient mHealth Apps to Electronic Health Record Systems. Appl Clin Inform 2015;6: 488–505http://dx.doi.org/10.4338/ACI-2014-12-RA-0115
Keywords: Mobile health; delivery of health; heart failure